Association Between Dietary Adherence and Blood Glucose Levels Among Patients with Type 2 Diabetes Mellitus - Farida Latif (Jurnal Ilmu Kesehatan Nusantara, 2024)
Background: Type 2 Diabetes Mellitus (T2DM) is a major public health problem worldwide. Poor dietary adherence remains one of the leading causes of uncontrolled blood glucose levels, increasing the risk of both microvascular and macrovascular complications. Understanding the relationship between dietary adherence and glycemic control is essential for improving diabetes management in primary healthcare settings. Research Objective: This study aimed to determine the association between dietary adherence and blood glucose levels among patients with Type 2 Diabetes Mellitus attending a primary healthcare center in Kendari City, Southeast Sulawesi, Indonesia. Methods: This analytical observational study employed a cross-sectional design involving 40 patients with Type 2 Diabetes Mellitus selected using purposive sampling. Dietary adherence was assessed using a structured questionnaire based on national diabetes dietary guidelines, while blood glucose levels were obtained from patients' medical records. Descriptive statistics were used to summarize respondent characteristics, and the Chi-square test was performed to analyze the association between dietary adherence and blood glucose levels at a significance level of p<0.05. Results: Among the respondents, 57.5% demonstrated poor dietary adherence, while 62.5% had uncontrolled blood glucose levels. Bivariate analysis revealed a significant association between dietary adherence and blood glucose levels (p=0.004). Patients with poor dietary adherence were 8.71 times more likely to have uncontrolled blood glucose levels than those with good dietary adherence (OR=8.71; 95% CI=1.95–38.91). Conclusion: Dietary adherence is significantly associated with blood glucose control among patients with Type 2 Diabetes Mellitus. Strengthening nutrition education, individualized dietary counseling, and family-supported diabetes self-management programs is recommended to improve glycemic control and reduce diabetes-related complications in primary healthcare settings.